An environmental assessment of the impacts of corruption, foreign investment inflow and trade liberalization in the rapidly emerging Malaysian Economy - Gyamfi, Bright Akwasi; Onifade, Stephen Taiwo; Ridzuan, Abdul Rahim; Shaari, Mohd Shahidan; Jena, Pabitra Kumar (Springer, 2023)
In the wake of various catastrophic consequences of climate change, Malaysia, a rapidly developing economy, is also inevitably experiencing environmental degradation that merits prompt and serious attention from policymakers and its government. Hence, this study simultaneously highlights the short and long-run dynamic connections between carbon emission in Malaysia and the trio of corruption levels, foreign investment inflow, and trade liberalization. The study also controls for a combination of other factors including energy use, GDP, and urbanization. A robust empirical analysis was conducted on time series observations for the country based on the recent Dynamic ARDL simulation. It was observed that Malaysia's per capita pollution levels significantly reduces based on the corruption perception levels during the sampling period while the economic expansion’s effect on emission levels is positive. Additionally, urbanization, trade levels and energy use all aggravate the emission levels. On the other hand, although FDI poses an insignificant environmental damage in the short run, its environmental sustainability enhancement roles were supported by its long-run negative impacts on carbon emission. Lastly, the EKC was established and as such, essential policy directions were provided for stakeholders in the rapidly emerging Malaysian economy.
Keywords: Carbon emission; Foreign investment infow; Trade liberalization; Malaysia; corruption; fi=Taloustiede|en=Economics|